Synbiotic preparation with lactic acid bacteria and inulin as a functional food: In vivo evaluation of microbial activities, and preneoplastic aberrant crypt foci - Chaiyasut C. (2017)
© 2017, Sociedade Brasileira de Ciencia e Tecnologia de Alimentos, SBCTA. All rights reserved. Host microbiome and metabolome are associated with the incidence of colorectal cancer (CC), one of the major health problems in developed countries. The pro and prebiotic supplementation helps to improve the host health. Inulin is one such prebiotic used for the enhancement of naïve probiotic bacterial population. This paper explains the impact of inulin (PRE) extracted from Jerusalem artichoke (JA), Lactobacillus plantarum HII11 (PRO), and synbiotic (SYN; inulin + L. plantarum HII11) preparation on Azoxymethane mediated CC induced rat model with respect to changes in microbial load, microbial enzymes, and preneoplastic aberrant crypt foci. The results suggested that the PRE and SYN supplementation effect ively reduced the selected pathogenic bacteria (Salmonella spp., and Escherichia coli), microbial enzymes and increased the probiotic load. The intervention of SYN significantly reduced the colonic ACF in CC model. The study results revealed that the supplementation of SYN diet (inulin and L. plantarum HII11) protects the AOM-mediated colon cancer induced host.